Pyroxazone, a new neuroprotective compound from Streptomyces sp. RAN54. (November 2018) - Hayakawa, Yoichi; Kuriyama, Taishin; Ibusuki, Yuta; Kimata, Shoko
Abstract A neuroprotective compound designated pyroxazone (1 ) was isolated from the culture broth ofStreptomyces sp. RAN54. The molecular formula of1 was established as C18 H14 N2 O5 by high-resolution FAB-MS. The structure was determined to be a new 2-amino-3H -phenoxazin-3-one derivative by NMR spectroscopic analysis. Pyroxazone (1 ) protected C6 rat glioma cells and N18-RE-105 rat primary retina-mouse neuroblastoma hybrid cells from glutamate-induced toxicity with EC50 s of 8.2 µM and 1.7 µM, respectively.